Entrepreneurial Government and Work Culture on Local Government - Anwar Sadat (Journal of Governance, 2022)
The government would face the society who smarter (knowledge based society) and the society who higher demanding (demanding community). To response those, the government should change the way to look, behavior, and the way to manage the public sector in a modern way. This study aims to describe and analyze the perspective of the government bureaucracy officials to accept and understand the concept of entrepreneurial government and to understand the factors explaining the understanding and attitude of the government bureaucracy officials in accepting the concept of entrepreneurship government. The method applied in this study was descriptive-qualitative with interview, observation and documentation data collection techniques. the data source and the population were all structural officials in the regional government of Baubau. According to the analysis and interpretation, it was found that the understanding and knowledge of the officials on the concept of entrepreneurial government in general was low. This was illustrated by the many officials who did not understand the ideas existing in entrepreneurial government. It was the consequence of the concept rarely introduced (lack of socialization) into the government bureaucracy of Baubau, lack of competence and the existence of a unconducive paternalistic bureaucratic culture to grow and develop this concept in the government bureaucracy. To provide the understanding and knowledge of government officials regarding the concept of entrepreneurial government, it is recommended that the Government should actively socialize this concept to the officials. Hence, displacing the paternalistic culture to a culture of respecting the innovation, creativity and work ethic by changing the values, symbols, and incentive system existing in the government bureaucracy